Patient Clinical Data Integration in Integrated Electronic Medical Record System for Health Care Facilities in Indonesia - Kurniadi, Arif; Pratiwi, Retno (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Complete patient service requires continuous support of clinical history. This can be realized by integrating electronic medical record data. The limitation is the wide variety of software, formats, and data dictionaries used in healthcare facilities. This was a descriptive analysis study with cross sectional approach to find open source electronic medical record integration model for clinical data exchange between health care facilities. Respondents were doctors, nurses, pharmacists, laboratory staffs, and person in charge of hospital information system as informant for content analysis. From the study, we managed a web-based service portal to implement clinical data integration that can be accessed by clinician registered within the Ministry of Health. The patient’s clinical history is stored in the hospital database and requires unique OpenIDRM code on the Health Service Server to integrate it. OpenIDRM contains all of the patient’s medical record number, as one patient may have several different medical record numbers in several hospitals. In conclusion, clinician can access the patient’s clinical history by opening a web portal system through a unique OpenIDRM code.